درس الشرط بين البصريين والكوفيين في منهاج تدريس النحو العربي في الجزائر The Conditional Lesson Between The Basrians And The Kufians In The Arabic Grammar Curriculum In Algeria - مفتاح, مولدي; بوبكر, حسيني (جامعة الوادي - University of Eloued, 2021)
يتحدث المقال عن إشكالية تدريس النحو العربي في مرحلة التعليم الثانوي في الجزائر وفق المنهجين البصري والكوفي دون تحديد مرجعية محددة له انطلاقا من درس الشرط، متبعين في ذلك المنهج الوصفي التحليلي، معتمدين على رصد آراء المذهبين البصري والكوفي في المسائل المتعلقة بموضوع الشرط مع ترجيح الرأي الذي يتوافق مع القدرات الذهنية للطلبة. وهدفْنا من خلال البحث لفت نظر خبراء المناهج التعليمية إلى هذه الإشكالية التي تعيق الطلبة في فهم الدروس النحوية. وخلصنا إلى ضرورة تبني مرجعية واضحة مع ترجيحنا-بناء على ما تم معالجته- المقاربة الكوفية في تناول موضوع الشرط لما فيه من يسر الفهم والاستيعاب. The article talks about the problem of teaching Arabic grammar in secondary education in Algeria according to the two approaches : Al-Basri and Al-Kufi without defining a specific reference for it, based on the conditional lesson following the descriptive and analytical approach, relying on monitoring the views of both: the Basrian and the Kufic doctrines on the issues related to the lesson of the conditional giving priority to the opinion that is compatible with the mental capabilities of the students. Our aim, through the research, is to draw attention of the educational curriculum experts towards the problem that hinders students from understanding grammatical lessons.
مقال
Keywords: الشرط، البصريين، الكوفيين، المنهاج، النحو; the conditional, Basrians, Kufians, curriculum, grammar.